Unformatted text preview: y you take the derivative with respect to y and treat everything else (including x) as a constant. 1. U = x 2 + y 2 MU x = 2x + 0 = 2x MU y = 2y 2. U = 5x 3 – 2y + 3y 2 MU x = 15x – 0 + 0 = 15x 2 MU y = 0  2 +6y = 6y2 3. U = 5xy + 6x 2 + 2y 3 MU x = 5y + 12x + 0 = 5y + 12x MU y = 5x + 6y 2 4. U = 10xy MU x = 10y MU y = 10x 5. U = 15x + 6y + 9x 2 y MU x = 15 + 18xy MU y = 6 +9x 2 6. U = 26x – 16y 2 MU x = 26 MU y = 32y 7. U = .5x 2 y MU x = xy MU y = .5x 2...
View
Full Document
 Fall '10
 Laury
 Economics, Microeconomics, Utility, MUy, Mux, Dr. Laury

Click to edit the document details